The Sepharadi and Oriental Jewish heritage - O Editor (Revista de História, 1983)
Ben Ami, Issachar (org. ), The Sepharadi and Oriental Jewish heritage. Studies  Jerusalem, The Magnes Press, The Hebrew University, 1982.